Team management and its role in the effectiveness of the organization An analytical study of the opinions of a sample of employees at Asiacell Communications Company - Omar Mustafa Mohammed; Halat Saeed Mohammed Saleh; Jamal Ahmad Hama Karim (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
In the middle of the last century, administrative development has contributed to the focus on the human element and its role in achieving the success and growth of business organizations. The technical developments and the numerous changes in the environment surrounding the organizations have led to several problems that necessitate attention to the human element and focus on the development and organizational effectiveness. Hence, many business organizations around the world have sought to adopt the work teams’ methodology by integrating individual capabilities into collaborative activities to mobilize and employ these talents and capabilities to enhance organizational effectiveness continuously. Given the importance of the above, the present study sought to determine the relationship and the impact between the work team management and organizational effectiveness of managers and employees in business organizations. To achieve this goal; the (60) questionnaire form was distributed for managers and employees and the valid of it to collect data reached (45) questionnaire at Asiacell Communications Company in Sulaymaniyah city. The results confirmed that the greater the interest in the work teams and their peaceful management, the more positive impact they have on enhancing organizational effectiveness. Based on the results of the research, several recommendations were made, the most important is the need to encourage flexibility and openness in the organizational relations between members and activate; this is it through the development of training programs that emphasize the principle of participation in the production of new ideas.